EBook Interaction Logs as a Tool in Predicting Learner Performance in Reading. - Al-Ahdal, Arif Ahmed Mohammed Hassan (Asiatic: IIUM Journal of English Language & Literature, 2020)
The present study assessed the effectiveness of ebook interaction logs in the reading performance of Saudi EFL learners. It employed an experimental research design to a total of 30 male students at Qassim University, Saudi Arabia, spanning twelve weeks. We used the BookRoll system and asked the EFL teachers to upload textbook materials, allowing learners free access anytime, anywhere. Apart from availability, what set the system apart from classroom teaching was the kind of privacy and individual learning pace that the system provides to learners: They managed to revisit relevant sections marked by the teacher, checked out the notes and engaged (even repeatedly) in other reading-related activities that the teacher incorporated into the ebook. The study analysed the system logs to develop prevalent reading patterns and predict reading behaviours in the participants. It shed light on the strategies that learners employed in reading the texts. The result showed that BookRoll could be used to predict learners' reading behaviours with a reasonable degree of accuracy which would be beneficial to a large number of interested parties including, but not restricted to, educational advisors keen to integrate technology into the EFL classroom in the Kingdom of Saudi Arabia, the teaching community which, for the most part, ignores reading as a skill by resorting to quick summaries in students' mother tongue at times and learners who need to find their individual learning pace and environment.